IMPLICATIONS FOR FINANCING RESULTS ON MUDHARABAH FINANCING VOLUME IN BANK MANDIRI SYARI’AH - Ani Lusiani; Sumarni Sumarni (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2020)
This research is motivated by the decrease of mudharabah financing volume from 2013-2015, while the share of financing increased except in 2014 at Bank Syariah Mandiri. From the observation while the researchers there is a negative relationship, whereas some previous research mentions that there is a positive relationship between the volume of financing mudharabah with profit sharing. It is very interesting writer to know more in relation volume of financing mudharabah with profit sharing at Bank Syariah Mandiri year 2012-2015. The method used is correlational descriptive method. The data used are monthly financial report of mudharabah financing and profit sharing of Bank Syari'ah Mandiri in 2012-2015. Data collection techniques used are document studies with data collection instruments browsing. Data analysis used descriptive statistic with Spearman Rank correlation technique, because the data of distributed research is not normal. The descriptive statistics of mudharabah financing volume data and the share of financing at Bank Syariah Mandiri from January 2012 to December 2015 have increased and decreased. Spearman Rank correlation calculation results for the relationship of mudharabah financing volume with the financing sharing at Bank Syariah Mandiri in 2012-2015 is equal to -0.259 with a significance level of 0.046 at the level of 5% confidence. The conclusion is the volume of mudharabah financing with profit sharing in Bank Syariah Mandiri in 2012-2015 has a weak correlation with a negative direction of -0.259 or -25.9%.